MENGENAL LEBIH DINI KANKER LEHER RAHIM BERSAMA FORUM KAJIAN DAN KOMUNIKASI MUSLIMAH - W. Winarni; Kanthi Suratih (P3M Universitas Aisyiyah Surakarta, 2020)
Cervical cancer is a health issue for women around the world. In Indonesia, the case of cervical cancer ranks first with a number of cases 14,368 people. Of that amount, 7,297, died, and the prevalence of 10,823 people every year. A simple method of early detection of cancer of the cervix is quite effective for today's society IVA (Visual inspection with acetic acid). This method is already standardized, tested and expressed easier, simpler, and cheaper than the pap smear test. The methods used in this activity is healthy talk and the introduction ofÂ how to sign symptoms of cervical cancer early. The model is developed in this activity Talkshow and Brainstorming. The targets are forÂ the mother's in the Forum for study and communication of Muslim Pucangan Kartosuro. The purpose of these activities are the participant has the ability to know the telltale symptoms of cervical cancer early and to having curiousity to detect cervical cancer early and understand what should they do if they find another signs of symptoms of cervical cancer.